Studi Hadis-Hadis Tentang Anjuran Berenang - Qhoirin Anisa; Muhammad Taufik (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Among the sports recommended by the Prophet Muhammad in the hadith is swimming. In a hadith narrated by Nasa’I and Ahmad ibn Hanbal it is states that swimming is include in a game that does not contain futility and is recommended to teach it to children. However, the hadith regarding the recommendation to swim contains irregularities in the Shahihain book, there are only recommendations for horse riding and archery, but in other reports there is the word swimming. This research examines the hadiths advising swimming, and reviews the understanding of these hadisths with the implementation of swimming in the present. The type of research with the takhrij and ma’anil hadith approaches. The results o this study indicate that the hadith studied regarding the recommendation to swim is found in two hadith source books, namely Sunan Kubra Nasa’I and Musnad Ahmad ibn Hanbal. The suggestion to swim has something to do with the hadith of the primacy of war in the ocean, as there was a fleet during the time of the caliph Ummar bin Khattab. Then swimming at the present time is included in the category of sports that have many benefits, but the thing that needs to be considered in swimming is to keep away harm to avoid immorality. Pay attention to clothes when going to do siwmming, as well as places that don’t mix.